2016
DOI: 10.1111/aec.12330
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of shade, water and soil type on emergence and early survival of three dominant species of the Atacama Desert

Abstract: Understanding the regeneration niche of species may allow us to gain insight into how communities are structured. In deserts, the regeneration niche is usually related to spaces beneath shrubs where shade cast by shrubs creates microenvironments that benefit seedlings and where even small amounts of rain may favour germination and establishment. Shade and water may also interact with different types of soils. However, species may have different requirements for germination and seedling survival. We could expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The dual response showed that slight shading increased the values of leaf traits and severe shading decreased them to that in full light conditions in a few species. In a given community, plant species usually present specific differences in response to light demand or shading tolerance; these differences may affect the responses of species that co-occurred across the shading gradients [14,15,19]. For seedlings of tropical tree species [7], the largest changes in most species in this study were observed to occur at relatively high light conditions compared to in low light conditions (3-12% daylight).…”
Section: Changes Of Trait Mean Along Shading Gradientsmentioning
confidence: 71%
See 1 more Smart Citation
“…The dual response showed that slight shading increased the values of leaf traits and severe shading decreased them to that in full light conditions in a few species. In a given community, plant species usually present specific differences in response to light demand or shading tolerance; these differences may affect the responses of species that co-occurred across the shading gradients [14,15,19]. For seedlings of tropical tree species [7], the largest changes in most species in this study were observed to occur at relatively high light conditions compared to in low light conditions (3-12% daylight).…”
Section: Changes Of Trait Mean Along Shading Gradientsmentioning
confidence: 71%
“…Meanwhile, vegetation restoration with diverse tree species requires long-term successions, and seedling survival and growth are critical for successful community establishment in the early stages [17]. Excessive radiation can generate stress in plant individuals and communities; thus, shading is a necessary and effective method of protecting seedlings [6,18,19]. Shade effects are also considered as key determinants of organ functional differentiation, individual performance, and community dynamics [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%